The sirtuin family members SIRT1, SIRT3 and SIRT6: Their role in vascular biology and atherogenesis. (October 2017) - Sosnowska, Bożena; Mazidi, Mohsen; Penson, Peter; Gluba-Brzózka, Anna; Rysz, Jacek; Banach, Maciej
Abstract: The sirtuins, silent mating-type information regulation 2 (SIRTs), are a family of nicotinamide adenine dinucleotide (NAD + )-dependent histone deacetylases with important roles in regulating energy metabolism and senescence. Activation of SIRTs appears to have beneficial effects on lipid metabolism and antioxidants, prompting investigation of the roles of these proteins in atherogenesis. Although clinical data are currently limited, the availability and safety of SIRT activators such as metformin and resveratrol provide an excellent opportunity to conduct research to better understand the role of SIRTs in human atherosclerosis. Encouraging observations from preclinical studies necessitate rigorous large, prospective, randomized clinical trials to determine the roles of SIRT activators on the progression of atherosclerosis and ultimately on cardiac outcomes, such as myocardial infarction and mortality. Highlights: The sirtuins (SIRTs) are a family of nicotinamide adenine dinucleotide (NAD + )-dependent histone deacetylases. SIRTS have important roles in regulating energy metabolism and senescence. Activation of SIRTs appears to have beneficial effects on lipid metabolism and antioxidants. The availability and safety of SIRT activators provide opportunity to better understand the role of SIRTs in atherosclerosis.